DOES DIGITAL BANKING AFFECT THE VALUE OF VALUE OF BANKING COMPANIES IN THE CURRENT ERA? - Andrew, Richard; Murwaningsari, Etty (Jurnal Akuntansi Kontemporer, 2024)
Research Purposes The purpose of this research is to analyse the relationship between digital banking and the value of banking organisations as a function of information asymmetry and cautious accounting.Research Methods. Using a quantitative methodology and 184 samples drawn from the IDX IC Indonesia Stock Exchange's panel/pooling data set covering the years 2018–2022, this research draws conclusions. E-Views data processing 12.Research Results and Findings. While information asymmetry does not have the potential to adversely implication the company's worth, the investigation reveals that Prudence accounting and digitization of banking may have a positive and substantial implication. Given that these final discovery, it's clear that digitising banking is crucial in the modern banking industry for increasing firm value and helping the community.